Design and implement of integrative access layer in campus network - Zhong-nan FU; Qun SHANG; Xu-xiao GONG (Tongxin xuebao)
At the moment,the access layer network in campus network has some problems,including hysteretic wireless network,resource deployment imbalance between the wired network and wireless network and weak support for private local network.To resolve these problems and make the access layer network satisfy the developing user request better,we give the definition of the integrative access layer network and implement it in Peking University.The result shows that the integrative access layer network works well and improves the service provided by campus network.